Polarity of amber mutations in ribosomal protein genes of Escherichia coli. - Cabezón, T (1980)
Two amber mutations have been mapped inside the spcA-strA region (now called rpsE-rpsL) on the bacterial genome. Derivatives of the transducing phage lambda fus3 carrying each mutation were constructed and assayed in ultraviolet-irradiated bacteria to identify the mutated genes and measure the polarity of the mutations. The data indicated that both mutations, 3162(Am) and 3161(Am), affect genes coding for ribosomal proteins: rplC (L3) and rpsN (S14), respectively. It was shown also that each mutation exerts, inside of its respective operon (S10 and spc units), a relatively strong polar effect on genes distal to the mutated locus.